The Role of Interpersonal Communication, Social Skills, and Inclusive Teacher Competence in Student Satisfaction at the School of Human - Rani, Ima; Asih, Daru; Andriyansah (Ilomata International Journal of Social Science, 2025)
The decline in student satisfaction rates with the School of Human Services has encouraged researchers to dig deeper into the variables that influence student satisfaction at the School of Human. Through this research, researchers want to examine the variables of interpersonal communication, social skills, and inclusive teacher competence concerning the school of human student satisfaction. This research method uses regression analysis, where the researcher wants to test the relationship between independent and dependent variables partially. The results of hypothesis testing in this research provide interesting results. Teacher social skills and interpersonal communication significantly influence student learning satisfaction, while teacher competence does not have a considerable impact. This highlights teachers' importance in communicating and socializing with students to create a satisfying learning environment. The results of this study provide an in-depth understanding of how teachers' interpersonal communication and social skills significantly impact student learning satisfaction. In addition, the fact that teacher competency does not considerably influence highlights that being smart in a subject is insufficient. Teachers must also be able to interact with students effectively to increase their learning satisfaction.